THE RELATIONSHIP BETWEEN MENTAL STATUS AND QUALITY OF LIFE AMONG THE ELDERLY - yudara sandra; Yoga Darmayura; Ayu Putri Wulandari (Nursing Sciences Journal, 2026)
Mental status is an psychological condition in terms of thinking, behavior, and adaptation to life pressures. Quality of life is a level of well-being in terms of physical, psychological, social, and environmental aspects. Older adults are vulnerable to mental disorders due to physical and social changes and the loss of a spouse, which can lead to a decline in quality of life. This study is important given the increasing number of elderly people and the high risk of mental health problems. The purpose of this study was to determine the relationship between mental status and quality of life among elderly people in the working area of the Mengwi I Badung Community Health Center. The study used a cross-sectional design with 215 respondents. The research instruments used were the SRQ and WHOQOL-BREF. The Spearman Rho test results showed a significant relationship between mental status and quality of life (p = 0.001; r = -0.864). The worse the mental status, the lower the quality of life of the elderly. The results of this study provide an important basis for efforts to improve psychosocial support and mental health for the elderly.